Technology, Chemistry and Bioactive Properties of Large Cardamom (Amomum subulatum Roxb.): An Overview - Gautam, Nawaraj; Bhattarai, Rewati Raman; Khanal, Bal Kumari Sharma; Oli, Prakash (International Journal of Applied Sciences and Biotechnology, 2016)
Large cardamom (Amomum subulatum Roxb.) is an aromatic and medicinal spice native to Eastern Himalayas belonging to the family Zingiberaceae. It is used as flavoring and preservative to different types of coffee, liquors, confections, beverages and tobacco. Volatile oil (2-4%) is the principal aroma-giving compound in large cardamom and 1,8- cineole is the major active compound in an extent 60 to 80% of the total volatile oil. Alcohol and aqueous extract of large cardamom have been reported to contain allopathic, analgesic, anti-inflammatory, antimicrobial, antioxidant, antiulcer, cardio-adaptogenic and hypolipidaemic activities. Large cardamom and its powder, oleoresin and essential oils have many culinary and therapeutic uses. Objective of this review is to give short overview on the processing technology, chemistry, bioactivity and uses of large cardamom and its components. Int J Appl Sci Biotechnol, Vol 4(2): 139-149